The ASEAN Intergovernmental Commission on Human Rights : institutionalising human rights in Southeast Asia - Tan, Hsien-Li, 1979- (New York : Cambridge University Press, 2011)
'This assessment of progress in Southeast Asia on human rights begins in the wake of the'Asian values' debate and culminates in the formal regional institutionalisation of the ASEAN Intergovernmental Commission on Human Rights (AICHR). Chapters examine the arduous negotiation of AICHR, the evolving relationship between ASEAN states' and the international human rights system, and the historical and experiential reasons for hesitancy. The text concludes with a discussion of how the evolving right to development impacts upon AICHR and international human rights in general, and how their preference for economic, social and development rights could help ASEAN states shape the debate'--
Machine generated contents note: 1. Charting the human rights institutionalisation process in Southeast Asia; 2. Enough of'Asian values': roots of the ASEAN states' reticence towards human rights; 3. Self-determination and democracy: the human rights experiences of five ASEAN states; 4. Instituting the Regional Rights Regime: the ASEAN Intergovernmental Commission on Human Rights and the role of civil society; 5. Human rights understanding between the ASEAN region and the United Nations: convergence, regional cohesion and national responsibility; 6. The unexplored aspect of human rights: what ASEAN needs to understand about the right to development; 7. Sustaining AICHR's substantive empowerment: implementation, integration, and international law.
Keywords: ASEAN. -- Intergovernmental Commission on Human Rights; Human rights -- Southeast Asia